Community psychology and community mental health : towards transformative change - Nelson, Geoffrey B. (Geoffrey Brian); Kloos, Bret; Ornelas, Jose (Advances in community psychology series., 2014)
"Mental health practices and programs around the world face growing criticism from policymakers, consumers, and service providers for being ineffective, overly reliant on treatment by professionals, and overly focused on symptoms. Many have called for new paradigms of mental health and new practices that can better support recovery, community integration, and adaptive functioning for persons diagnosed with psychiatric disabilities. While there has recently been much discourse about transformation and recovery, there has yet to be a critical and systematic review that unpacks the concept of mental health systems transformation or that examines strategies for how to create transformative change in mental health. Community Psychology and Community Mental Health provides empirical justification and a conceptual foundation for transformative change in mental health, based on community psychology values and principles of ecology, collaboration, empowerment, and social justice. Chapters provide strategies for making changes at the level of society, policy, organizations, community settings, and mental health practices. The editors and authors draw from experience in different countries in recognition of the need to tailor change strategies to different contexts. The common experiences of the international perspectives represented underscore the importance and the need for a new paradigm while demonstrating that there are many alternatives and opportunities for pursuing transformative change. This book will be of interest to community mental health professionals, researchers, and students, as well as policymakers, administrators, and those with lived experience of mental health issues"--